Long‐term efficacy (up to 68 weeks) of Baricitinib in combination with topical corticosteroids in adult patients with moderate‐to‐severe atopic dermatitis: Analysis of treatment responders, partial responders and nonresponders originating from study BREEZE‐AD7. (20th January 2023) - Silverberg, Jonathan I.; Simpson, Eric L.; Thyssen, Jacob Pontoppidan; Werfel, Thomas; Cardillo, Tracy E.; Colvin, Stephanie; Pierce, Evangeline; Chen, Yun‐Fei; Chen, Sherry; Eichenfield, Lawrence
Abstract: Background: Baricitinib demonstrated efficacy in treating adults with moderate‐to‐severe atopic dermatitis (AD) in Phase 3 clinical trials. Objective: To examine long‐term efficacy of baricitinib combined with topical corticosteroids (TCS) in adult patients from a Phase 3 study, BREEZE‐AD7 (NCT03733301), enrolled in ongoing extension study, BREEZE‐AD3 (NCT03334435). Methods: Upon BREEZE‐AD7 completion, responders or partial responders (RPR [vIGA‐AD™ ≤2]) receiving baricitinib 2‐mg or 4‐mg + TCS maintained their original treatment doses in BREEZE‐AD3. Nonresponders (NR; vIGA‐AD 3, 4) receiving baricitinib 2‐mg were rerandomized 1:1 to baricitinib 2‐mg or 4‐mg; NR receiving baricitinib 4‐mg remained on same dose. Integrated data from all patients (RPR + NR = baricitinib 4‐mg intent‐to‐treat [ITT] cohort) receiving continuous baricitinib 4‐mg in BREEZE‐AD7 through BREEZE‐AD3 were analysed, along with baricitinib 4‐mg or 2‐mg RPR cohorts. Primary endpoint was proportion of patients with vIGA‐AD (0, 1) at Weeks 16, 36 and 52 (Weeks 32, 52 and 68 of continuous therapy). Additional outcomes included improvement in EASI75 and Itch NRS (up to Week 32). Missing data were imputed by last observation carried forward. Results: In baricitinib 4‐mg ITT cohort ( N  = 102), proportions of patients achieving vIGA‐AD (0, 1) at Week 32, Week 52, and Week 68 were 21.6%, 26.5% and 23.5%; EASI75 were 46.1%, 40.2% and 43.1%, respectively. Itch NRS ≥4‐point improvement (Itch ≥4) were 47.3% at Week 16 and 40.6% at Week 32. In baricitinib 4‐mg RPR cohort ( N  = 63), proportions of patients achieving vIGA‐AD (0, 1) at Week 32, Week 52 and Week 68 were 31.7%, 33.3% 34.9%, respectively; EASI75 were 57.1%, 49.2% and 49.2%, respectively. Itch ≥4 were 53.6% at Week 16 and 46.4% at Week 32. Corresponding proportions for baricitinib 2‐mg RPR cohort ( N  = 53) for vIGA‐AD (0, 1) were 39.6%, 45.3% and 30.2%; EASI75 were 77.4%, 69.8% and 58.5%, respectively. Itch ≥4 were 56.3% at Week 16 and 47.9% at Week 32. Conclusion: Baricitinib 4‐mg and 2‐mg combined with TCS maintained clinically meaningful sustained efficacy over 68 weeks of continuous treatment.